Effect of a maternal and newborn health system quality improvement project on the use of facilities for childbirth: a cluster‐randomised study in rural Tanzania. Issue 5 (11th March 2019) - Larson, Elysia; Gage, Anna D.; Mbaruku, Godfrey M.; Mbatia, Redempta; Haneuse, Sebastien; Kruk, Margaret E.
Abstract: Objectives: Reduction in maternal and newborn mortality requires that women deliver in high quality health facilities. However, many facilities provide sub‐optimal quality of care, which may be a reason for less than universal facility utilisation. We assessed the impact of a quality improvement project on facility utilisation for childbirth. Methods: In this cluster‐randomised experiment in four rural districts in Tanzania, 12 primary care clinics and their catchment areas received a quality improvement intervention consisting of in‐service training, mentoring and supportive supervision, infrastructure support, and peer outreach, while 12 facilities and their catchment areas functioned as controls. We conducted a census of all deliveries within the catchment area and used difference‐in‐differences analysis to determine the intervention's effect on facility utilisation for childbirth. We conducted a secondary analysis of utilisation among women whose prior delivery was at home. We further investigated mechanisms for increased facility utilisation. Results: The intervention led to an increase in facility births of 6.7 percentage points from a baseline of 72% (95% Confidence Interval: 0.6, 12.8). The intervention increased facility delivery among women with past home deliveries by 18.3 percentage points (95% CI: 10.1, 26.6). Antenatal quality increased in intervention facilities with providers performing an additional 0.5 actions across the full population and 0.8 actions for the home delivery subgroup. Conclusions: We attribute the increased use of facilities to better antenatal quality. This increased utilisation would lead to lower maternal mortality only in the presence of improvement in care quality.